Efficiency of Standard Operating Procedure (SOP) and Work Motivation on Remote Working Systems at PT Ghania Creative Indonesia with Work Training as An Intervening Variable - Rizky Sahputra Ginting; Darmilisani Darmilisani; Emi Wakhyuni (Utan Kayu Publishing, 2025)
This study aims to analyze the effect of the efficiency of the implementation of Standard Operating Procedures (SOP) and work motivation on the remote working system at PT Ghania Creative Indonesia, with work training as an intervening variable. The quantitative method with an associative approach was used in this study using a sample of 66 employees of PT Ghania Creative Indonesia. The research data were collected using a questionnaire method that had been tested for validity and reliability. The use of the PLS-SEM analysis method in this study provided research results that the implementation of Standard Operating Procedures (SOP) and work motivation had a positive effect on the remote working system at PT Ghania Creative Indonesia (R2 = 0.615), both directly and through work training as an intervening variable. Work training has been shown to strengthen the relationship between SOP and work motivation on the remote working system, with test results showing strong predictive relevance (Q2 = 0.512) and a significant effect between variables. These findings emphasize the importance of integrating SOP, work motivation, and training in creating a productive and efficient remote working system